2006
DOI: 10.1016/j.pec.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

A course of instruction for women with irritable bowel syndrome

Abstract: IBS may be of benefit for the patients, and could be a part of a multicomponent approach in the treatment of this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(50 reference statements)
0
28
0
2
Order By: Relevance
“…On returning, the practitioner "removed" the placebo needles and exchanged a few words of encouragement. Specific cognitive and behavioural interventions that might be beneficial for irritable bowel syndrome (such as relaxation, 16 cognitive behavioural therapy, 17 or education/counselling 18 ) were not allowed.…”
Section: Group 3 (Augmented Interaction)mentioning
confidence: 99%
“…On returning, the practitioner "removed" the placebo needles and exchanged a few words of encouragement. Specific cognitive and behavioural interventions that might be beneficial for irritable bowel syndrome (such as relaxation, 16 cognitive behavioural therapy, 17 or education/counselling 18 ) were not allowed.…”
Section: Group 3 (Augmented Interaction)mentioning
confidence: 99%
“…Subsequent normalisation of their HRQOL at follow-up might be due to adequate treatment, receiving a diagnosis and information about the nature of their disease, or being taken care of. Bengtsson et al [46] have shown that being taken care of, and information/education, improves women's quality of life when suffering from functional diseases.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although nursing management of IBS patients has been reported to be adequate and efficient the diagnosis must first of all be confirmed before treatment is established for these patients. 5,7 Although there many IBS patients referred to specialists, and they constitute about half of all patients, the most efficient strategy still seems to be to program one initial visit to a specialized physician for a final judgement and then personalize care. 1 Clinically, specialists in gastroenterology have a tendency to reject patients admitted for suspected IBS at once, and they expect these patients to be handled at primary care centers.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are involved directly in the planning and implementation of therapeutic interventions for this patient population, and they can help patients with IBS by teaching them to help themselves. [4][5][6][7] The question is whether it is necessary to refer all these patients to gastroenterologists, or whether primary care physicians and other subspecialist physicians could make a fair judgment of the patients' health problems and offer care management.…”
Section: Introductionmentioning
confidence: 99%